Solusi Model Aliran Gas Dalam Pipa pada Kondisi Line Packing Menggunakan Skema Richtmyer - Harry Budiharjo Sulistyarso; Suryasatriya Trihandaru; Leksono Mucharam; Septoratno Siregar; Ivanky Saputra; Sinatra Canggih (Institute for Research and Community Services (LPPM) ITB, 2004)
Line packing is a process storing gas in pipeline by increasing inlet gas flow rate while outlet gas flow rate is kept constant. This difference of gas flow rate causes the gas flow in pipeline being transient. Line packing process is intended to guarantee gas supply when trouble occurs. In this paper, a transient model with boundary condition is solved numerically using Richtmyer scheme, because stability analysis showed that Richtmyer scheme is better than other explicit schemes. In the case presented, it is shown that Richtmyer scheme sufficiently agrees with the real data in gas pipeline transmission, which is in many cases unsteady-state.